Note—Optimal Inventories Based on Job Completion Rate for Repairs Requiring Multiple Items - Smith, Stephen A.; Chambers, John C.; Shlifer, Eli (Management Science, 1980)
A model is formulated for optimizing multi-item inventories for repair of field equipment based on holding costs and the probability of job completion without stockout. This results in a different type of objective function from those found in most inventory problems in that the contributions of different line items are not separable. It is shown, however, that the optimal policy has the same form as the one that results from standard marginal analysis solutions in which the objective function is separable.